The Terminal Oxidase cbb(3) Functions in Redox Control of Magnetite Biomineralization in Magnetospirillum gryphiswaldense - Li, Yingjie (American Society for Microbiology, 2014)
The biomineralization of magnetosomes in Magnetospirillum gryphiswaldense and other magnetotactic bacteria occurs only under suboxic conditions. However, the mechanism of oxygen regulation and redox control of biosynthesis of the mixed-valence iron oxide magnetite [FeII(FeIII)(2)O(4)] is still unclear. Here, we set out to investigate the role of aerobic respiration in both energy metabolism and magnetite biomineralization of M. gryphiswaldense. Although three operons encoding putative terminal cbb(3)-type, aa(3)-type, and bd-type oxidases were identified in the genome assembly of M. gryphiswaldense, genetic and biochemical analyses revealed that only cbb(3) and bd are required for oxygen respiration, whereas aa(3) had no physiological significance under the tested conditions. While the loss of bd had no effects on growth and magnetosome synthesis, inactivation of cbb(3) caused pleiotropic effects under microaerobic conditions in the presence of nitrate. In addition to their incapability of simultaneous nitrate and oxygen reduction, cbb(3)-deficient cells had complex magnetosome phenotypes and aberrant morphologies, probably by disturbing the redox balance required for proper growth and magnetite biomineralization. Altogether, besides being the primary terminal oxidase for aerobic respiration, cbb(3) oxidase may serve as an oxygen sensor and have a further role in poising proper redox conditions required for magnetite biomineralization.